Oligomerization-primed coiled-coil domain interaction with Ubc13 confers processivity to TRAF6 ubiquitin ligase activity. Issue 1 (December 2017) - Hu, Lin; Xu, Jiafeng; Xie, Xiaomei; Zhou, Yiwen; Tao, Panfeng; Li, Haidong; Han, Xu; Wang, Chong; Liu, Jian; Xu, Pinglong; Neculai, Dante; Xia, Zongping
Abstract Ubiquitin ligase TRAF6, together with ubiquitin-conjugating enzyme Ubc13/Uev1, catalyzes processive assembly of unanchored K63-linked polyubiquitin chains for TAK1 activation in the IL-1R/TLR pathways. However, what domain and how it functions to enable TRAF6's processivity are largely uncharacterized. Here, we find TRAF6 coiled-coil (CC) domain is crucial to enable its processivity. The CC domain mediates TRAF6 oligomerization to ensure efficient long polyubiquitin chain assembly. Mutating or deleting the CC domain impairs TRAF6 oligomerization and processive polyubiquitin chain assembly. Fusion of the CC domain to the E3 ubiquitin ligase CHIP/STUB1 renders the latter capable of NF-κB activation. Moreover, the CC domain, after oligomerization, interacts with Ubc13/Ub~Ubc13, which further contributes to TRAF6 processivity. Point mutations within the CC domain that weaken TRAF6 interaction with Ubc13/Ub~Ubc13 diminish TRAF6 processivity. Our results reveal that the CC oligomerization primes its interaction with Ubc13/Ub~Ubc13 to confer processivity to TRAF6 ubiquitin ligase activity. Ubiquitin ligase TRAF6 catalyzes assembly of free polyubiquitin chains for TAK1 activation in the IL-1R/TLR pathways, but the mechanism underlying its processivity is unclear. Here, the authors show that TRAF6 coiled-coil oligomerization domain primes its interaction with Ubc13/Ub~Ubc13 to confer processivity.